Comparison of Seismic Analysis And Design Outputs Using IS 1893(Part 1): 2016 And NBC 105:2020 Codes Using Finite Element Software - Shah, Prasham; Karki, Sudarshan; Magar, Rojit; Pathak, Shree Krishna; Sherpa, Nimnuri; Keshari, Nitesh Kumar; Dhakal, Binaya Prasad (Journal of Advanced College of Engineering and Management, 2025)
Nepal is located in one of the most seismically active regions in the world and has experienced numerous destructive earthquakes throughout its history. The 1988 earthquake, with a magnitude of 6.8, highlighted the urgent need for earthquake-resistant design standards, leading to the introduction of the Nepal National Building Code (NBC 105:1994) [3]. Despite the availability of a national seismic code, many engineers in Nepal continue to rely on the Indian Standard (IS 1893) due to familiarity and lack of local implementation experience. The diverse architectural styles and varying shapes and sizes of buildings in Nepal further increase their vulnerability to seismic forces, making proper code adoption critical for ensuring structural safety. This study focuses on the comparison of seismic performance of a five-story residential building located in Seismic Zone V , characterized by Type III soil conditions according to IS 1893:2016 and in Kathmandu, characterized by Type C soil conditions according to NBC 105:2020. The main objective of this research is to compare the updated Nepal National Building Code NBC 105:2020 with the Indian Standard IS 1893 (Part 1):2016 in terms of structural response and design requirements. The Response Spectrum Method is employed using ETABS software to evaluate key parameters, including base shear, storey displacement, storey drift, and reinforcement requirements. By systematically analyzing the building under both codes, the study provides a detailed understanding of how the choice of code affects structural behavior during seismic events. The results reveal that buildings designed according to NBC 105:2020 experience higher base shear and greater storey displacements and drifts compared to those designed with IS 1893:2016. Additionally, the NBC code generally requires higher quantities of reinforcement, reflecting its more conservative approach to earthquake-resistant design. These findings emphasize the importance of adopting context-specific seismic design standards that consider local geological and seismic conditions. The study provides valuable insights for engineers, policymakers, and stakeholders, highlighting the need for careful code selection to ensure both safety and economic efficiency in building construction in Nepal.